Visualizations of Chinese nation branding: A comparative study of the 2008 and 2022 Beijing Olympic Games opening ceremonies - Han Xie (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2024)
As Beijing became the first city in history to successfully host both Summer and Winter Olympic Games, this paper looks into the different visualizations of the two Olympics opening ceremonies in 2008 and 2022. By incorporating the concept of Nation Branding, it features a comparative case study to discuss how China has understood and branded the country through detailed and well-rehearsed artistic presentations in these events. The case study mainly focuses on three layers: role conception, role perception / the formation of brands, and finally the presentation of strategically designed brands. Each layer of comparison answers a specific question, and their combination in turn answers how the difference in artistic presentation may connect with the shifting Chinese nation branding strategies. The result of this paper suggests that the presentations in 2008 and 2022 Olympics opening ceremonies, as the focus shifted from "country and heroism" to "people and togetherness," generally stood in line with the nation branding strategies performed by the Chinese government throughout this 14-year span.
Keywords: 330